Quantitative analysis of 3‐OHB[a]P and (+)‐anti‐BPDE as biomarkers of B[a]P exposure in rats. (20th October 2015) - Lin, Qi; Xiao‐Chen, Liu; Bo, Yang; Na, Liu; Min, Shi; Gang, Chen; Hui, Liu; Jie, Zhou; Fa‐Sheng, Li
Abstract: The aim of this study was to develop an analytical method for the determination the levels of metabolites of benzo[a]pyrene (B[a]P), 3‐hydroxybenzo(a)pyrene (3‐OHB[a]P) and (+)‐ anti ‐benzo(a)pyrene diol‐epoxide [(+)‐ anti ‐BPDE, combined with DNA to form adducts], in rat blood and tissues exposed to B[a]P exposure by high‐performance liquid chromatography with fluorescence detection (HPLC/FD), and to investigate the usefulness of 3‐OHB[a]P and (+)‐ anti ‐BPDE as markers of intragastrical exposure to B[a]P in rats. The levels of 3‐OH‐B[a]P and B[a]P‐tetrol I‐1 released after acid hydrolysis of (+)‐ anti ‐BPDE in the samples were measured by HPLC/FD. The calibration curves were linear ( r 2 > 0.9904), and the lower limit of quantification ranged from 0.34 to 0.45 ng/mL for 3‐OHB[a]P and from 0.43 to 0.58 ng/mL for (+)‐ anti ‐BPDE. The intra‐ and inter‐day stability assay data suggested that the method is accurate and precise. The recoveries of 3‐OHB[a]P and (+)‐ anti ‐BPDE were in the ranges of 73.6 ± 5.0 to 116.5 ± 6.3% and 73.3 ± 8.5 to 141.2 ± 13.8%, respectively. A positive correlation was found between the concentration of intragastrical B[a]P and the concentrations of 3‐OH‐B[a]P and (+)‐ anti ‐BPDE in the blood and in most of the tissues studied, except for the brain and kidney, which showed no correlation between B[a]P and 3‐OHB[a]P and between B[a]P and (+)‐ anti ‐BPDE, respectively. A sensitive, reliable and rapid HPLC/FD was developed and validated for analysis of 3‐OHB[a]P and (+)‐ anti ‐BPDE in rat blood and tissues. There was a positive correlation between the concentration of 3‐OHB[a]P or (+)‐ anti ‐BPDE in the blood and the concentration of 3‐OHB[a]P or (+)‐ anti ‐BPDE in the most other tissues examined. The concentration of 3‐OHB[a]P or (+)‐ anti ‐BPDE in the blood could be used as an indicator of the concentration of 3‐OHB[a]P or (+)‐ anti ‐BPDE in the other tissues in response to B[a]P exposure. These results demonstrate that 3‐OHB[a]P and (+)‐ anti ‐BPDE are potential biomarkers of B[a]P exposure, which would also be useful to assess the carcinogenic risks from B[a]P exposure. Copyright © 2015 John Wiley & Sons, Ltd.